Transcranial Focused Ultrasound (tFUS) and Transcranial Unfocused Ultrasound (tUS) Neuromodulation: From Theoretical Principles to Stimulation Practices - di Biase, Lazzaro; Falato, Emma; Di Lazzaro, Vincenzo (Frontiers in Neurology, 2019)
Transcranial focused ultrasound is an emerging technique for non invasive neurostimulation. Compared to magnetic or electric non invasive brain stimulation, this technique has an higher spatial resolution and can reach deep structures. In addition, both animal and human studies suggest that, potentially, different site showed that every site of central or peripheral nervous system, can be targeted by this technique. Depending on stimulation parameters transcranial focused ultrasound is able to determine a wide spectrum of effects, ranging from suppression or stimulation facilitation of neural activity to tissue ablation. The aim is to review the state of the art of human transcranial focused ultrasound neuromodulation literature, exploring the theoretical principles which underlie the explanation of the bioeffect on neural tissues, and showing the stimulation techniques and parameters used and their outcome in term of clinical, neurophysiological or neuroimaging results and safety.